2016
DOI: 10.2174/1874350101609010084
|View full text |Cite
|
Sign up to set email alerts
|

Can Parenting Styles Affect the Children’s Development of Narcissism? A Systematic Review

Abstract: Abstract:The aim of this paper is to define whether different types of parenting styles (and which ones) affect the child's development in the direction of narcissism, through a systematic review of the studies on the subject in the literature, considering only research published from the Nineties to today. The ten studies considered in this review are representative of the main approaches used to investigate the association between parenting and the emergence of narcissistic features in children. These studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous theoretical and empirical research has also demonstrated important links between parenting and narcissism (Claudio, 2016;Kernberg, 1975;Millon, 1981), with likely variation dependent on how narcissism is defined. Narcissism is a constellation of personality traits that include an inflated sense of self-worth, a lack of concern or empathy for others, entitlement, and seeking admiration of others (American Psychiatric Association, 2013).…”
Section: A Proposed Spectrum Of Parenting Practicesmentioning
confidence: 99%
“…Previous theoretical and empirical research has also demonstrated important links between parenting and narcissism (Claudio, 2016;Kernberg, 1975;Millon, 1981), with likely variation dependent on how narcissism is defined. Narcissism is a constellation of personality traits that include an inflated sense of self-worth, a lack of concern or empathy for others, entitlement, and seeking admiration of others (American Psychiatric Association, 2013).…”
Section: A Proposed Spectrum Of Parenting Practicesmentioning
confidence: 99%
“…Thus, a clinician-structured point-of-view is seen as a rich source of information for a complete assessment. characteristics, such as attachment state of mind, specific parenting style, and mental health or at-risk behaviors [14] deeply influence parent-child relationships and, consequently, child development [15][16][17]. These authors also underlined that this relationship is determined by a child's specific characteristics, such as temperament [18], methods of communication and interaction with caregivers or other people, and emotional regulation functioning [19].…”
Section: Introductionmentioning
confidence: 99%